2017
DOI: 10.1007/s11356-017-8490-y
|View full text |Cite
|
Sign up to set email alerts
|

Looking for phosphate-accumulating bacteria in activated sludge processes: a multidisciplinary approach

Abstract: Over the past decades, an increasing need in renewable resources has progressively appeared. This trend concerns not only fossil fuels but also mineral resources. Wastewater and sewage sludge contain significant concentrations in phosphate and can be considered as a fertilizer source of the utmost importance. In wastewater treatment plants, the biological uptake of phosphate is performed by a specific microbiota: the phosphate-accumulating organisms. These microorganisms are recovered in sewage sludge. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In order to satisfy the increasingly stringent environmental regulations and mitigate the occurrence of eutrophication, various physicochemical technologies, including precipitation method, biological remediation, membranes, ion exchange, and coagulation, have been developed for efficient sequestrating of phosphate from polluted waters. However, the established treatment methods usually suffer from some unavoidable limitations, such as slow kinetics, insufficient capture capacity, and poor specificity as well as the production of large amount of solid sludge, which needs the subsequent dispose and thus causes secondary environmental risks. Moreover, it is technically difficult for these water treatment technologies mentioned above to reduce phosphates below the acceptable level (0.5–1.0 ppm) recommended by the World Health Organization (WHO).…”
Section: Introductionmentioning
confidence: 99%
“…In order to satisfy the increasingly stringent environmental regulations and mitigate the occurrence of eutrophication, various physicochemical technologies, including precipitation method, biological remediation, membranes, ion exchange, and coagulation, have been developed for efficient sequestrating of phosphate from polluted waters. However, the established treatment methods usually suffer from some unavoidable limitations, such as slow kinetics, insufficient capture capacity, and poor specificity as well as the production of large amount of solid sludge, which needs the subsequent dispose and thus causes secondary environmental risks. Moreover, it is technically difficult for these water treatment technologies mentioned above to reduce phosphates below the acceptable level (0.5–1.0 ppm) recommended by the World Health Organization (WHO).…”
Section: Introductionmentioning
confidence: 99%
“…Although the pure culture of Accumulibacter are still not available, but they are frequently enriched in EBPR systems and typically represent 5-20% of bacterial community (He et al, 2008;Nielsen et al, 2010). Tarayre et al, 2017 reported the presence of bacteria belonging to phyla α-Proteobacteria, β-Proteobacteria, and Sphingobacteria in EBPR. Several other bacterial; strains belonging to genera Acinetobacter, Corynebacterium, and Pseudomonas have been reported with the presence of polyphosphate granules of size nearly 100 nm as evident through electron microscopy (Tarayre et al, 2017).…”
Section: Application Of Phosphate Accumulating Microbesmentioning
confidence: 99%
“…Tarayre et al, 2017 reported the presence of bacteria belonging to phyla α-Proteobacteria, β-Proteobacteria, and Sphingobacteria in EBPR. Several other bacterial; strains belonging to genera Acinetobacter, Corynebacterium, and Pseudomonas have been reported with the presence of polyphosphate granules of size nearly 100 nm as evident through electron microscopy (Tarayre et al, 2017). Staphylococcus aureus can store upto 93 mM phosphates in their storage granules; it has been recorded to remove upto 81% of phosphate from the polyphosphate accumulating medium.…”
Section: Application Of Phosphate Accumulating Microbesmentioning
confidence: 99%
“…Currently, phosphate removal methods include precipitation, biological treatment, crystallization, membrane technology and adsorption methods (Huang et al, 2017;Tarayre et al, 2017). However, other methods have more limitations than the adsorption method.…”
Section: Introductionmentioning
confidence: 99%